Serum Cytokine and Chemokine Profile in Relation to the Severity of Coronavirus Disease 2019 in China. (21st June 2020) - Chi, Ying; Ge, Yiyue; Wu, Bin; Zhang, Wenshuai; Wu, Tao; Wen, Tian; Liu, Jingxian; Guo, Xiling; Huang, Chao; Jiao, Yongjun; Zhu, Fengcai; Zhu, Baoli; et al.
Abstract: Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We investigated the serum cytokine and chemokine levels in asymptomatic, mild, moderate, severe, and convalescent SARS-CoV-2–infected cases. Proinflammatory cytokine and chemokine production induced by SARS-CoV-2 were observed not only in symptomatic patients but also in asymptomatic cases, and returned to normal after recovery. IL-6, IL-7, IL-10, IL-18, G-CSF, M-CSF, MCP-1, MCP-3, IP-10, MIG, and MIP-1α were found to be associated with the severity of COVID-19. Moreover, a set of cytokine and chemokine profiles were significantly higher in SARS-CoV-2–infected male than female patients. The serum levels of MCP-1, G-CSF, and VEGF were weakly and positively correlated with viral titers. We suggest that combinatorial analysis of serum cytokines and chemokines with clinical classification may contribute to evaluation of the severity of COVID-19 and optimize the therapeutic strategies. Abstract : The serum levels of IL-6, IL-7, IL-10, IL-18, G-CSF, M-CSF, IP-10, MCP-1, MCP-3, MIG, and MIP-1α were associated with the severity of COVID-19. Men had higher levels of cytokines/chemokines than women. Some cytokines/chemokines were weakly correlated with the viral load.